Evaluating Modi’s Foreign Policy: Continuity or Change - Farhat Konain Shujahi; Nazir Hussain (Journal of Political Studies, 2016)
The foreign policy of India has seen tremendous transformation under Modi’s premiership underscoring that leadership plays a pivotal role in elevating the stature of a country. Modi’s slogan of ‘Shining India’ signifies India’s aspiration for acquiring great power status in international system and vision of leadership to make it happen. He has drastically shifted India’s foreign policy from slow to steady approach. India’s growing confidence and vigor to aspire a leading role in the world is evident in provocations of the leadership. Modi’s pro-active policy and worldwide initiatives reflect India is outreaching/ expanding diplomatic clout, winning the support of allies and revitalizing economic policy hence making India a rapidly growing economy in the world within two years since the current government has taken office. The success of Modi government will lie in turning the world in its favor and projecting India’s soft image through raising distinct voice at international level, achieving climate change and economic development goals and strengthening elements of national power domestically. The pitfalls of current policies centered at aggravating communalism, humanitarian issues and religion oriented politics may impede India’s long term struggle. The real victory of Modi’s government will lie in his dealing with contemporary challenges at domestic, regional and international level.